PENGARUH DIGITAL MARKETING DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA UMKM BANDENG PRESTO - Ghazien, Fuadhi; Puspitasari, Ratih Hesty Utami; Akbar, Shofif Sobarrudin (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This research aims to determine the effect of digital marketing and product quality on purchase desicions with customer satisfaction as an intervening variable at UMKM Bandeng Presto in Semarang. The researcher used primary data obtained through the distribution of questionnaire forms via Google Form to customer at UMKM Bandeng Presto in Semarang. The population in this study were customer at UMKM Bandeng Presto in Semarang. The technique used in sampling was probability sampling using cluster sampling with an MOE formula of 96 customer. The analysis tool used in this study used SmartPLS 4. The results of this study are H1; digital marketing has no significant effect on purchasing decisions, H2; product quality has a significant effect on purchasing decisions, H3; customer satisfaction has a significant effect on purchasing decisions, H4; digital marketing has a significant effect on customer satisfaction, H5; product quality has a significant effect on customer satisfaction, H6; customer satisfaction has a significant mediating effect on digital marketing on purchasing decisions and H7; customes satisfaction has a significant mediating effect on product quality on purchasing decisions